Laravel Api Masterclass: Autentikasi, Role-Based Access and Crud Testing - Apriliano, Yova Rezky; Azima, Fauzan; Zahran, Fikry Muhammad; Zikri, Muhammad; Risanty, Rita Dewi; Sutrisno, Mirza; Mujiastuti, Rully; Nurbaya Ambo, Sitti; Ardharani, Yana (Edumedia Solution, 2025)
The latest developments in web technology require mastery in the development of well-planned and secure APIs as a foundation for integrating various digital systems. However, many new developers have difficulty in understanding the basic principles and practices of creating web-based APIs. To fulfil this need, the service team organised an event entitled